Development of Natural Bioactive Alkaloids: Anticancer Perspective - Patel, Ashish; Vanecha, Ravi; Patel, Jay; Patel, Divy; Shah, Umang; Bambharoliya, Tushar (Mini Reviews in Medicinal Chemistry, 2022)
Abstract: Cancer is a frightful disease that still poses a 'nightmare' worldwide, causing millions of casualties annually imposing one of the human race's greatest health-care challenges that entail a pragmatic treatment strategy. Plants are repositories for new chemical entities and have a promising cancer research path, supplying 60% of the anticancer agents currently used. However, plants and plant-derived products revolutionize the field, as they are quick, cleaner, eco-friendly, low-cost, effective, and less toxic than conventional treatment methods. Alkaloids are important chemical compounds that serve as a rich reservoir for drug discovery and development. However, some alkaloids derived from natural herbs display anti-proliferation and antimetastatic activity on different forms of cancer both in vitro and in vivo. Alkaloids have also been widely formulated as anticancer medications, such as camptothecin and vinblastine. Based on the information in the literature, this review focuses on the naturally-derived bioactive alkaloids with prospective anticancer properties. Still, more research and clinical trials are required before final recommendations can be made on specific alkaloids.
Keywords: camptothecin